Effects of post‐release movements on survival of translocated sage‐grouse. Issue 6 (17th July 2019) - Ebenhoch, Kyle; Thornton, Daniel; Shipley, Lisa; Manning, Jeffrey A.; White, Kevin
ABSTRACT: Translocation is a vital tool in conservation and recovery programs, and knowledge of factors that determine demographic rates of translocated organisms is important for assessing the efficacy of translocations. Greater sage‐grouse ( Centrocercus urophasianus ) have been the subject of recent translocation efforts because of their declining range and their usefulness as an umbrella species for conservation. Using a long‐term data set on sage‐grouse in central Washington, USA, we compared movement and demographic rates of translocated and resident birds. Because newly translocated birds experience physiological stress during translocation and are released in unfamiliar habitat, we hypothesized their demographic rates would differ from residents. We analyzed 18 years of radio‐tracking data acquired from resident, newly translocated (<1 yr post‐translocation; T1), and previously translocated (>1 yr post‐translocation; T2) sage‐grouse between 1989 and 2017 to estimate movement rates, survival, and productivity. Newly translocated sage‐grouse exhibited farther daily movements (0.58 km/day) and smaller 95% home ranges (89 km 2 ) than residents and previously translocated birds. Daily movements and sex influenced survival, but survival did not differ according to residency status. Furthermore, birds that survived to a second year after translocation exhibited shorter daily movements compared to their first year ( β ˆ  = −0.727 ± 0.157 [SE]), which corresponded with increased survival the second year (T1 = 0.526, T2 = 0.610). This decrease in movements and increase in survival the second year was not apparent in the control group of resident birds, indicating a possible behavioral link to survival of newly translocated sage‐grouse. Most productivity metrics were similar for translocated and resident birds, except for nest propensity (i.e., nest initiation rate), which was lower for newly translocated birds (35%) compared to residents and previously translocated birds. Our results reveal that translocated sage‐grouse exhibit temporary differences in some demographic parameters in their first year, which later align with those of resident birds in subsequent years. Similarities in adult and nest survival according to residency status further suggest that translocation may prove to be a viable tool for restoring and conserving this species. Continued declines in sage‐grouse populations in Washington, however, indicate that habitat conversion and fragmentation may be reducing demographic rates of residents and translocated birds, which warrants further study. © 2019 The Wildlife Society. Abstract : Sex and movement were important to sage‐grouse survival and movement differed between translocated and resident individuals. Translocated sage‐grouse adjusted to the release site after roughly 1 year and subsequently modified their movements to increase their probability of survival.